(untitled) (La Rivada, 2025)
This study presents three main objectives: to identify the notion of disability constructed by people with disabilities during their university life; to scrutinize the meaning that social support networks hold for people with disabilities throughout university life; and to analyze the impact of social support networks in the consolidation of university experiences. The methodological approach is qualitative, using grounded theory as the research framework. Data collection was through a semi-structured interviews conducted with students with disabilities attending the Faculty of Social Sciences of the National University of San Juan. The main findings indicate the predominance of hegemonic theoretical models on disability during the course of the students’ university life, and the incidence of social support networks on decision-making processes.